Qualification of the family caregiver to the application of the Educational Technology in Health - Paula Dayanna Sousa dos Santos; Zélia Maria de Sousa Araújo Santos; Léa Maria Moura Barroso Diógenes; José Manuel Peixoto de Caldas; Kátia Alves Ferreira Rodrigues; Rithianne Frota Carneiro
ABSTRACT Objective: To evaluate the changes in the participation of the family caregiver in the treatment of the hypertensive person with the application of the Educational Technology in Health (ETH). Method: Participant research carried out in a Primary Health Care Unit with 11 family caregivers (FC). The ETH was elaborated based on health education and applied in ten meetings between June and August 2016. We organized the results into categories. Results: FCs experienced learning experiences through the exchange of information, socialization of experiences, and linkage establishments. The FCs were encouraged to share their doubts and experiences, so that, supported by listening to the professional, they felt welcomed and determined to fulfill their role with hypertensive relatives. Final considerations: The changes that have taken place have been highlighted in the learning of FCs and their commitment to family and self-care, as well as to the conviction that the family environment is indicated to make these changes effective.